PENGUJIAN EFEK MARKETING MIX DAN PERLINDUNGAN PADA SEKTOR RETAIL DI KOTA BATAM SEBAGAI SUATU KAJIAN SINTESA META ANALYSIS - Putu Hari Kurniawan; Heryenzus Heryenzus (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2018)
This research is to purpose the small retail distribution who have always worked to establish close relationship with customer throught the Retail Marketing mix. Thus the literature has a long tradition of testing the effect of various instrument on Retail Patronage. This Meta-Study synthesis prior research into one comprehensive frame work. We use 120 responden which evaluate from 4 district extracted from 250 shopper to test the impact of 24 marketing mix instrument on retail patronage. Specifically, we investigate the direct and indirect effect in marketing mix of these instrument display to observe strongest effect of most outcome variable whereas price, communication service, WOM, hedonic behaviour, retail environment and other especially in Batam. To resolve the problem in the research we used Structure Equation Model (SEM) with Covarian basic approach.